2013
DOI: 10.15309/13psd140101
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual/Religious Coping and Breast Cancer: A Systematic Literature Review

Abstract: SPIRITUAL/RELIGIOUS COPING AND BREAST CANCER:A SYSTEMATIC LITERATURE REVIEW ABSTRACT-This systematic literature review aimed to examine the research published between 2006 and 2011 that investigated religious/spiritual coping (RSC) in female breast cancer patients and its effects in adaptation to the disease. The descriptive categories used were 'religious beliefs', 'spirituality', 'religiosity', 'religious experiences', 'religion', 'coping behavior', 'adjustment', 'breast cancer', 'religious coping' and 'spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Culturally, women are more resilient and, therefore, use positive RC strategies to deal with stress. (22) In a recent systematic review, Veit et al (23) reported greater use of positive RC in women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Culturally, women are more resilient and, therefore, use positive RC strategies to deal with stress. (22) In a recent systematic review, Veit et al (23) reported greater use of positive RC in women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%